ROLE OF PARENTING STYLES IN PATIENTS WITH YOUNG ONSET SUBSTANCE USE DISORDER (CAHIERS MAGELLANES-NS, 2024)
Background: Substance use in adolescents is a public health concern. It is on the rise in both developing and developed countries and is associated with adverse health and social outcomes. Parenting style is one of the important factors influencing adolescent substance use. Based on responsiveness and demandingness, there are four parenting styles- authoritarian, authoritative, permissive and neglectful. Aim: This study aims to estimate the prevalence of each parenting style in the context of young onset substance use disorder among patients attending tertiary health centre in Tamilnadu, India. Materials and Methods: A cross sectional study was done on 115 patients with young onset substance use (onset less than 25 years). Socio-demographic proforma, ASSIST, Leeds dependency questionnaire and PSDQ were used. Results: The maximum prevalence was seen in permissive parenting style. Authoritarian and permissive parenting were significantly associated with earlier age of onset of substance use, duration of substance use and family history of substance use. Authoritative parenting was associated with less number of substances. Conclusion: Parenting programs incorporating specific desired behaviours will help train parents on better monitoring and to prevent adverse outcomes in adolescents having substance use disorder